Adsorption and Vibration for S Atom on Rh Three Low-Index Surfaces - Yu, Shuaiqin; Jia, Xiangfeng; Dong, Lihua; Yin, Yansheng (Asian Journal of Chemistry, 2010)
All critical characteristics between S atom and Rh surfaces have been systematically studied by 5-parameter Morse potential. The calculated results show that S atom locates in the fourfold hollow site of the (100) surface. Different from the atoms in the first and second period, S atom tend to occupy the fourfold hollow site of (110) surface. For S-Rh(111) adsorption system, S atom adsorbs in the fcc and hcp threefold hollow sites and the two adsorption sites are found to be approximately equivalent. In accordence with the conclusion of S-Ni and Cl-Ag adsorption system, the surface binding energy of S atom is also found to be relevant to the coarse degree of cluster surface with the binding energy ordered as (111) < (100) < (110) in this paper.